Customer Focus On Internet Banking In Malaysia - Sudha, Raju (2005)
This study deliberates on the customer focus of Internet banking in Malaysia. The study is a qualitative empirical research on the development of Internet banking in Malaysia. The results of the survey indicate that most of the consumers are not opting for Internet banking as they prefer human interactions in their banking activity.The banks should, therefore, provide a human touch through video conferencing and they should not impose a fee for Internet banking transactions. The security features of Internet banking should be improved by building stronger firewalls to prevent hackers entering into Internet banking codes. Internet banking should be user-friendly so as to entice more clients to use their services.